A COMPARATIVE STUDY EXAMINING THE UZBEK VERSION OF DAN BROWN’S THE DA VINCI CODE AND HOW IT REFLECTS THE ORIGINAL WORK - Khayrullayeva Mohinur Akmal Qizi; Sh. Khushmurodova (TADQIQOTLAR, 2025)
Annotation: This study explores how Dan Brown’s novel The Da Vinci Code has been translated into Uzbek, comparing the original and translated versions through their linguistic, cultural, and thematic aspects. It examines how the translator balances staying true to the original text with adapting the story so that it feels natural, engaging, and meaningful to Uzbek readers.